Multi-informant validity evidence for the SSIS SEL Brief Scales across six European countries - Anthony, Christopher J.; Elliott, Stephen N.; Yost, Michayla; Lei, Pui-Wa; DiPerna, James C.; Cefai, Carmel; Camilleri, Liberato; Bartolo, Paul A.; Grazzani, Ilaria; Ornaghi, Veronica; Cavioni, Valeria; Conte, Elisabetta; et al. (Frontiers in Psychology, 2022)
The SSIS SEL Brief Scales (SSIS SELb; Elliott et al., 2020) are multi-informant (teacher, parent, student) measures that were developed to efficiently assess the SEL competencies of school-age youth in the United States. Recently, the SSIS SELb was translated into multiple languages for use in a multi-site study across six European countries (Greece, Croatia, Italy, Latvia, Portugal, Romania). As such, the purpose of the current study was to examine concurrent and predictive evidence for the SEL Composite scores from the translated versions of the SSIS SELb Scales. Results indicated that SSIS SELb Composite scores demonstrated expected positive concurrent and predictive relationships with scores from the Connor-Davidson Resilience Scale (CD-RISC; Connor & Davidson, 2003) and negative relationships with scores from the problem behavior scales of the Strengths and Difficulties Questionnaire (SDQ; Goodman, 1997). Although there were a few exceptions, these patterns generally were consistent across informants (parents, teachers, students) and samples providing initial validity evidence for the Composite score from the translated versions of the SSIS SELb Scales. Limitations and future research directions are discussed.